2017
DOI: 10.1021/acs.biochem.6b01264
|View full text |Cite
|
Sign up to set email alerts
|

V67L Mutation Fills an Internal Cavity To Stabilize RecA Mtu Intein

Abstract: Inteins mediate protein splicing, which has found extensive applications in protein science and biotechnology. In the Mycobacterium tuberculosis RecA mini-mini intein (ΔΔIhh), a single valine to leucine substitution at position 67 (V67L) dramatically increases intein stability and activity. However, crystal structures show that the V67L mutation causes minimal structural rearrangements, with a root-mean-square deviation of 0.2 Å between ΔΔIhh-V67 and ΔΔIhh-L67. Thus, the structural mechanisms for V67L stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Previous studies on intein engineering have mostly focused on the conserved residues or neighboring exteins, this study suggests the feasibility of engineering controllable inteins by mutating the residues surrounding the conserved ones. As a further perspective, following the recent development of photocaged cysteine, tyrosine, and serine amino acid residues which have been introduced in living systems, light activated C‐terminal cleavage inteins may be obtained by incorporating these and other photocaged residues.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies on intein engineering have mostly focused on the conserved residues or neighboring exteins, this study suggests the feasibility of engineering controllable inteins by mutating the residues surrounding the conserved ones. As a further perspective, following the recent development of photocaged cysteine, tyrosine, and serine amino acid residues which have been introduced in living systems, light activated C‐terminal cleavage inteins may be obtained by incorporating these and other photocaged residues.…”
Section: Discussionmentioning
confidence: 86%
“…57 Biophysical characterization of the evolved mini-inteins suggests that the selected mutations are important to restore the structural stability of the intein overall while concomitantly restoring flexibility near the site of the deletion. [57][58][59][60][61][62] The Synechocystis sp. PCC6803 DnaB mini-intein was developed by deletion of its native HEN, with directed evolution experiments improving activity and flexibility of the intein insertion site.…”
Section: Resultsmentioning
confidence: 99%
“…The Mycobacterium tuberculosis RecA intein has a native HEN domain but has been engineered to splice in trans and to function as a mini-intein. , However, protein splicing of the engineered mini-intein was inefficient and required directed evolution experiments to optimize activity . Biophysical characterization of the evolved mini-inteins suggests that the selected mutations are important to restore the structural stability of the intein overall while concomitantly restoring flexibility near the site of the deletion. The Synechocystis sp. PCC6803 DnaB mini-intein was developed by the deletion of its native HEN, with directed evolution experiments improving the activity and flexibility of the intein insertion site. , Deletion of the HEN domain is deleterious in a variant of the Methanococcus jannaschii TFIIB intein, in which the part of the loop that replaces the HEN domain inserts as a β-strand into the HINT domain; the authors suggest that the native HEN domain could facilitate the proper folding of the pseudosubdomains of the HINT domain .…”
Section: Resultsmentioning
confidence: 99%
“…The authors observed that the V67L mutation did not affect the overall conformation but claim that it improved side chain packing . The suggestion that the bulkier side chain filled an internal cavity was further supported by high-pressure NMR measurements of the cavity volume change due to the V67L mutation, 13 ± 3 mL mol –1 , roughly corresponding to the size of a methylene group . The mutation demonstrated global NMR chemical shift perturbations, including active site residues, and slowed hydrogen–deuterium exchange, suggesting that global conformational dynamics were reduced .…”
Section: Discussionmentioning
confidence: 97%
“…27 The suggestion that the bulkier side chain filled an internal cavity was further supported by high-pressure NMR measurements of the cavity volume change due to the V67L mutation, 13 ± 3 mL mol −1 , roughly corresponding to the size of a methylene group. 35 The mutation demonstrated global NMR chemical shift perturbations, including active site residues, and slowed hydrogen−deuterium exchange, suggesting that global conformational dynamics were reduced. 36 This is in agreement with a recent computational study of the V67L intein, 37 where V67L reduced conformational fluctuation to various extents.…”
Section: ■ Discussionmentioning
confidence: 99%